2017
DOI: 10.1080/00207454.2017.1412964
|View full text |Cite
|
Sign up to set email alerts
|

Association between ABCB1 polymorphisms and response to first-generation antiepileptic drugs in a Tunisian epileptic population

Abstract: The G2677T T and C3435T T alleles as well as the TT, CTT and TTT haplotypes seemed to be significantly associated with drug-resistance epilepsy in our population. Genetic predisposition, involved in this resistance, may contribute to the establishment of a personal optimized therapy for newly diagnosed epileptic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 76 publications
13
21
1
Order By: Relevance
“…Epileptic syndromes represented only 26% of our epileptic patients, in fact that most of our patients with isolated seizures have no EEG results or have an EEG with no specific electroclinical syndrome. This result is similar to another study from the center of Tunisia (18.3%) [32]. The etiology remained unknown in 57% of our cases, in drug-resistant patients and drug-responsive ones (52% and 62%).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Epileptic syndromes represented only 26% of our epileptic patients, in fact that most of our patients with isolated seizures have no EEG results or have an EEG with no specific electroclinical syndrome. This result is similar to another study from the center of Tunisia (18.3%) [32]. The etiology remained unknown in 57% of our cases, in drug-resistant patients and drug-responsive ones (52% and 62%).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with epilepsy type, drug-resistant and drug-responsive patients showed a predominance of generalized seizures (84% vs. 66%), compared to focal (6% vs. 34%) and focal to bilateral tonic-clonic seizures (10% vs. 0%). Some studies provided the same results [74, 76, 77], while many others showed the opposite [32, 73, 75, 7882] due to some changes recently made in the classifications of epilepsies taken into account the type of onset seizures [32, 56]. Epileptic syndromes represented only 26% of our epileptic patients, in fact that most of our patients with isolated seizures have no EEG results or have an EEG with no specific electroclinical syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ABCC2 rs717620 -24 CT+TT genotypes and ABCC2 rs3740066 (3972C>T) CT+TT genotypes are overrepresented in epileptic patients resistant to antiepileptic drugs in the Chinese population, whereas ABCC2 rs2273697 (1249G>A) and ABCB1 rs1045642 (3435C>T) polymorphisms were not found to be associated with drug-resistant epilepsy in this population. The frequency of the haplotype TGT (ABCC2 -24C>T/ABCC2 1249G>A/ABCC2 3972C>T) in resistant patients is double that of responsive patients [309]. The TAGAA haplotype in CACNA1A accumulates in drug-resistant patients in the Chinese population [310].…”
Section: Epilepsymentioning
confidence: 99%